Character Education Development Model Based on Local Wisdom in Schools and Madrasahs - Herianto, Edy; Dahlan, Dahlan; Al-Qodri, Bagdawansyah; Setyowati, Rr. Nanik (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2021)
The problem examined in this study is the model of local wisdom-based education in schools and madrasahs? This research was conducted qualitatively with the type of phenomenology. Researchers analyzed all phenomena that were the focus of school and madrasah research. The results showed that of the four models developed by the Ministry of Education and Culture, teachers used three models in strengthening character education: integration in subjects, integration of character education through the development of school culture and learning activity centers, and integration of character education through learning activities. One model has not been functional, namely, the integration of character education in local content. The cause is the cultural diversity of students, the unavailability of guidelines for the use of local wisdom in learning activities, and the unavailability of technical models of character education that utilize cultural wisdom